Contextualization of Humanistic-Based Qur'anic Education for Adults in Palangka Raya - Lutfi, Saiful; Qodir, Abdul; Saihu, Made (ANDRAGOGI, 2025)
This study explores the implementation of humanistic principles in the teaching of the Qur'an for adult learners. Adopting a qualitative research approach, the study aims to understand how humanistic theories, such as those proposed by Maslow and Rogers, are applied within the context of Qur'anic education and how they influence the personal and spiritual development of adult learners. The subjects of this study were 20 adult learners from several institutions and 5 educators from local Islamic education institutions. Data collection methods included semi-structured interviews, observations, and documentation analysis, with a focus on capturing the lived experiences of participants and the dynamics of the learning process. Triangulation of data and member checking will be employed to ensure validity and credibility of the findings. The study found that applying humanistic education in Qur'anic learning enhanced adult learners' engagement, reflection, and personal connection to the text. It fostered deeper, more meaningful learning by prioritizing personal growth and relevance to daily life. This research shows that humanistic principles can enrich Qur'anic education, offering a transformative model that supports adult learners' spiritual and personal development in modern contexts.